The improvement of taxi service in Kuantan / Nizamuddin Zainuddin - Zainuddin, Nizamuddin (1985)
Commercial Vehicles Licensing Board plays a vital role in issuing taxi permit and Road Transport Department is responsible to surper- vise and control the taxi operation in order to ensure that satis factory level of taxi service is being served. Although different sort of regulations enforced and many methods of controlled have been implemented people still break the rules and making offences. Problems faced by taxi users in Kuantan are varried from problems faced by taxi users in Kuala Lumpur. This is due to the different demographic background and economic growth. In Kuala Lumpur demand for taxi service is surplus. Surplus to the extent that taxi drivers refuse to take any passengers. Taxi drivers didn't afraid to lose their passengers because they know there will always be other users to use their service.